Power-sharing executives : governing in Bosnia, Macedonia, and Northern Ireland - McEvoy, Joanne (National and ethnic conflict in the 21st century., 2015)
Based on interviews with power-sharing executives and external actors in Bosnia, Macedonia, and Northern Ireland, this in-depth study explores the challenges of promoting cooperation and accommodation between elites representing contending groups in deeply divided places.